Hematopoietic Cell-Specific SLC37A2 Deficiency Accelerates Atherosclerosis in LDL Receptor-Deficient Mice - Zhao, Qingxia; Wang, Zhan; Meyers, Allison K.; Madenspacher, Jennifer; Zabalawi, Manal; Zhang, Qianyi; Boudyguina, Elena; Hsu, Fang-Chi; McCall, Charles E.; Furdui, Cristina M.; Parks, John S.; Fessler, Michael B.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Macrophages play a central role in the pathogenesis of atherosclerosis. Our previous study demonstrated that solute carrier family 37 member 2 (SLC37A2), an endoplasmic reticulum-anchored phosphate-linked glucose-6-phosphate transporter, negatively regulates macrophage Toll-like receptor activation by fine-tuning glycolytic reprogramming in vitro. Whether macrophage SLC37A2 impacts in vivo macrophage inflammation and atherosclerosis under hyperlipidemic conditions is unknown. We generated hematopoietic cell-specific SLC37A2 knockout and control mice in C57Bl/6 Ldlr−/− background by bone marrow transplantation. Hematopoietic cell-specific SLC37A2 deletion in Ldlr−/− mice increased plasma lipid concentrations after 12-16 wks of Western diet induction, attenuated macrophage anti-inflammatory responses, and resulted in more atherosclerosis compared to Ldlr−/− mice transplanted with wild type bone marrow. Aortic root intimal area was inversely correlated with plasma IL-10 levels, but not total cholesterol concentrations, suggesting inflammation but not plasma cholesterol was responsible for increased atherosclerosis in bone marrow SLC37A2-deficient mice. Our in vitro study demonstrated that SLC37A2 deficiency impaired IL-4-induced macrophage activation, independently of glycolysis or mitochondrial respiration. Importantly, SLC37A2 deficiency impaired apoptotic cell-induced glycolysis, subsequently attenuating IL-10 production. Our study suggests that SLC37A2 expression is required to support alternative macrophage activation in vitro and in vivo. In vivo disruption of hematopoietic SLC37A2 accelerates atherosclerosis under hyperlipidemic pro-atherogenic conditions.